2017
DOI: 10.1007/s00109-017-1537-1
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis

Abstract: Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 44 publications
6
81
2
2
Order By: Relevance
“…The staining intensity of RRS1 expression was scored according to the following: score 0, negative staining; score 1, weak staining; score 2, moderate staining; and score 3, strong staining; the extent of staining was classified as the percentage of positive cells: score 0, 0; score 1, 1‐25%; score 2, 26‐50%; score 3, 51‐75%; and score 4, 76‐100%. The final quantitation of staining for each sample was obtained by multiplying the two scores . RRS1 expression was graded as high expression if the score >6; if the score ≤6, the case was classified as low expression.…”
Section: Methodsmentioning
confidence: 99%
“…The staining intensity of RRS1 expression was scored according to the following: score 0, negative staining; score 1, weak staining; score 2, moderate staining; and score 3, strong staining; the extent of staining was classified as the percentage of positive cells: score 0, 0; score 1, 1‐25%; score 2, 26‐50%; score 3, 51‐75%; and score 4, 76‐100%. The final quantitation of staining for each sample was obtained by multiplying the two scores . RRS1 expression was graded as high expression if the score >6; if the score ≤6, the case was classified as low expression.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this result, we found that HOXC6 is a master regulator of many genes, which have documented pro-tumorigenic functions. In our studies, we identified several genes, including CEACAM6, SPARC, WNT6, CST1, MMP2, and KRT13, which have been extensively studied and demonstrated to be involved in the regulation of tumor growth, migration and invasion, cell cycle, and apoptosis (Chang et al 2018;Choi et al 2009;Dai et al 2017;Kuo et al 2014;Rizeq et al 2018;Wang et al 2018;Yusuf et al 2014;. In other types of cancers, HOXC6 has also been shown to have the capacity to regulate these cancerrelated genes.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 87%
“…Breast cancer had serious adverse effects on the prognosis of patients (Dai et al, 2017). In recent years, proposal of molecular biomarkers had provided important clues for targeted therapy of breast cancer as well as other malignant tumors (Buzdin et al, 2018;Kutomi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%